Virtual communities concepts, methodologies, tools and applications - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This reference book thoroughly investigates the development, design, and utilization of virtual organizations and communities and the resulting impact of these venues by focusing on research on the foundation and future of social networking, human-computer interaction, and innumerable applications of virtual worlds"--Provided by publisher.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed Dec. 7, 2010).
Keywords: Online social networks; Electronic villages (Computer networks); Human-computer interaction; Internet -- Social aspects; Virtual reality -- Social aspects; Applications of virtual communities; Behavior in virtual communities; Communities of practice; Digital divide; Education in virtual communities; Privacy and security in virtual worlds; Social computing; Social software; Trust in virtual communities; User interface design; Electronic books